ChemInform Abstract: An Easy Access to Fluoroalkanes by Deoxygenative Hydrofluorination of Carbonyl Compounds via Their Tosylhydrazones. Issue 25 (3rd June 2013) - Yadav, Arvind K.; Srivastava, Vishnu P.; Yadav, Lal Dhar S.
Abstract An efficient synthesis of monofluoroalkanes (II) by deoxygenative hydrofluorination of carbonyl compounds via their tosylhydrazones surrogates (I) is presented.